The Effect of Cognitive Therapy on the Ability to Control Negative Thoughts in Low Self-Esteem Patients - Harianja, Susi Junita; Nasution, Siti Saidah; Daulay, Wardiyah (Poltekkes Kemenkes Tanjung Karang, 2024)
Low self-esteem is the appearance of negative thoughts about the meaning of self as a response to a situation. Negative thoughts can influence how you think about yourself and how you view the world and can interfere with work, study, and daily activities. Therapy is cognitively focused on helping the client identify and correct maladaptive thoughts, type automatic behaviors, and change behaviors caused by various​ emotional problems. This research aims to analyze the influence of cognitive therapy on the ability to control negative thoughts in low self-esteem patients. This research uses a quantitative quasi-experimental study with a pretest-posttest non-equivalent group control design. The sample for this study was 64 respondents from patients with low self-esteem who were hospitalized, divided into 32 intervention groups and 32 control groups. The sampling technique for this research uses purposive sampling. Research data collection used the ATQ-B-15 (Automatic Thoughts Questionnaire–Believability-15) instrument. Data were analyzed using descriptive statistics, dependent t-test, and independent t-test. The results showed a change in the intervention group's ability to control negative thoughts before and after cognitive therapy (t=15.84; p=0.00). There was a difference in the ability to control negative thoughts in the post-test of the control and intervention groups (Sig.2-tailed=0.00 or p-value<0.05). Giving cognitive therapy has a significant influence on reducing the ability to control negative thoughts in low self-esteem patients.